2011
DOI: 10.1097/rli.0b013e318200757a
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles Improve Sonothrombolysis In Vitro and Decrease Hemorrhage In Vivo in a Rabbit Stroke Model

Abstract: Introduction Tissue plasminogen activator (tPA) is the thrombolytic standard of care for acute ischemic stroke, but intracerebral hemorrhage (ICH) remains a common and devastating complication. We investigated using ultrasound (US) and microbubble (MB) techniques to reduce required tPA doses and to decrease ICH. Materials and Methods Fresh blood clots (3–5 hours) were exposed in vitro to tPA (0.02 or 0.1 mg/mL) plus pulsed 1 MHz US (0.1 W/cm2), with or without 1.12 × 108/mL MBs (Definity or albumin/dextrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 31 publications
2
65
0
Order By: Relevance
“…Two UCAs were used to nucleate cavitation, Definity V R and echogenic liposomes (ELIP). Definity V R , a commercially available UCA, has been shown previously to nucleate stable cavitation and enhance thrombolysis (Datta et al, 2008;Brown et al, 2011;Hitchcock et al, 2011). ELIP are potential theragnostic agents for the treatment of stroke Radhakrishnan et al, 2012;Kopechek et al, 2013) with the ability to encapsulate and release rt-PA upon exposure to ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Two UCAs were used to nucleate cavitation, Definity V R and echogenic liposomes (ELIP). Definity V R , a commercially available UCA, has been shown previously to nucleate stable cavitation and enhance thrombolysis (Datta et al, 2008;Brown et al, 2011;Hitchcock et al, 2011). ELIP are potential theragnostic agents for the treatment of stroke Radhakrishnan et al, 2012;Kopechek et al, 2013) with the ability to encapsulate and release rt-PA upon exposure to ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…A possible higher incidence of intracranial hemorrhage when using high frequency ultrasound as used in the study by Molina et al might be related to the enhanced effectiveness of TPA when administered in the presence of microbubbles. This supposition was supported by subsequent work of Culp et al, in a rabbit model of stroke, which showed that 1-Mhz ultrasound with TPA and microbubbles increases recanalization rates compared to ultrasound and TPA alone, without an increase in the incidence of intracranial hemorrhage [10]. They also showed effective sonolysis using microbubbles and ultrasound without TPA in a rabbit stroke model.…”
Section: Sonothrombolysis In Acute Ischemic Strokementioning
confidence: 68%
“…This can be achieved by the use of microbubbles [8,9], possibly even without the use of a fibrinolytic agent [10].…”
Section: Introductionmentioning
confidence: 99%
“…20 Low-intensity ultrasound combined with systemic delivery of microbubble contrast agents has been shown to improve thrombolysis in the presence or absence of tissue plasminogen activator (tPA) in the past. 7,19,20,24 The Combined Lysis of Thrombus in Brain Ischemia Using Transcranial Ultrasound and Systemic tPA (CLOTBUST) trial and the Transcranial Low-Frequency Ultrasound-Mediated Thrombolysis in Brain Ischemia (TRUMBI) trial with unfocused, low-frequency (300 kHz) ultrasound have shown some promise, but with complications such as increased hemorrhage rates. 1,18 HIFU as a stand-alone method for thrombolysis seems to be more advantageous, as it reduces the risk of hemorrhage by eliminating the side effects of thrombolytic drugs as well as adequately causing thrombolysis without damage to the targeted vessels.…”
Section: Ischemic Strokementioning
confidence: 99%